Lung Surfactant Lipids Provide Immune Protection Against Haemophilus influenzae Respiratory Infection - García-Fojeda, Belén; González-Carnicero, Zoe; de Lorenzo, Alba; Minutti, Carlos M.; de Tapia, Lidia; Euba, Begoña; Iglesias-Ceacero, Alba; Castillo-Lluva, Sonia; Garmendia, Junkal; Casals, Cristina (Frontiers in Immunology, 2019)
Non-typeable Haemophilus influenzae (NTHi) causes persistent respiratory infections in patients with chronic obstructive pulmonary disease (COPD), probably linked to its capacity to invade and reside within pneumocytes. In the alveolar fluid, NTHi is in contact with pulmonary surfactant, a lipoprotein complex that protects the lung against alveolar collapse and constitutes the front line of defense against inhaled pathogens and toxins. Decreased levels of surfactant phospholipids have been reported in smokers and patients with COPD. The objective of this study was to investigate the effect of surfactant phospholipids on the host-pathogen interaction between NTHi and pneumocytes. For this purpose, we used two types of surfactant lipid vesicles present in the alveolar fluid: i) multilamellar vesicles (MLVs, > 1 μm diameter), which constitute the tensioactive material of surfactant, and ii) small unilamellar vesicles (SUVs, 0.1 m diameter), which are generated after inspiration/expiration cycles, and are endocytosed by pneumocytes for their degradation and/or recycling. Results indicated that extracellular pulmonary surfactant binds to NTHi, preventing NTHi self-aggregation and inhibiting adhesion of NTHi to pneumocytes and, consequently, inhibiting NTHi invasion. In contrast, endocytosed surfactant lipids, mainly via the scavenger receptor SR-BI, did not affect NTHi adhesion but inhibited NTHi invasion by blocking bacterial uptake in pneumocytes. This blockade was made possible by inhibiting Akt phosphorylation and Rac1 GTPase activation, which are signaling pathways involved in NTHi internalization. Administration of the hydrophobic fraction of lung surfactant in vivo accelerated bacterial clearance in a mouse model of NTHi pulmonary infection, supporting the notion that the lipid component of lung surfactant protects against NTHi infection. These results suggest that alterations in surfactant lipid levels in COPD patients may increase susceptibility to infection by this pathogen.